L’Automédication aux Antibiotiques - BOURAI , Lycia; CHABI , Yasmine; BOUSSALEM , Laeticia; HANNACHI , Nadji (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine. Déppartement de Pharmacie, 2025)
Self-medication has become an increasingly dangerous trend. While tolerated for certain medications, self-medication involving antibiotics seriously jeopardize public health systems. This thesis aims to study the habits of 221 Algerian participants regarding self-medication with antibiotics and to identify the factors influencing this practice. Our survey reveals that 62% of participants use antibiotics without a prescription, with the majority being women. Adults aged 29 to 38, public sector employees, and healthcare professionals are the most affected. Self-medication rates do not appear to be influenced by the participants’ field of study or their health status. Amoxicillin is the most commonly used antibiotic in this context, mainly for symptoms that have previously been treated with the same antibiotic, such as sorethroats, which were among the most frequently reported. As for the pharmacist’s role, only 23% of respondents were denied the sale of an antibiotic, and only a minority were offered an alternative. These results highlight the urgent need for effective awareness campaigns on the proper use of antibiotics
التداوي الذاتي بالمضادات الحيوية يُعدّ ظاهرة خطيرة منتشرة في المجتمع الجزائري، ما يش ّكل تهديدًا حقيقيًا ل المستهلكين. يهدف هذا العمل إلى دراسة عادات 221مشاركًا جزائريًا وتحليل العوامل المؤثرة على هذه الممارسة. وقد كشفت نتائج الاستطلاع أن %62 من المشاركين يلجؤون إلى التداوي الذاتي، حيث تبيّن أن أغلبهم من النساء، والفئة العمرية الأكثر تمثي ًلا تتراوح بين 29و 38سنة، خاصة من فئة الموظفين والعاملين في القطاع الصحي. كما أظهرت الدراسة أن نوع التخصص الجامعي والحالة الصحية للمشاركين لا يؤثران بشكل ملحوظ على نسبة التداوي الذاتي. ويُعد الأموكسيسيلين من أكثر المضادات الحيوية استخدا ًما في هذا السياق، وغالبًا ما يُستعمل لعلاج أعراض سبق التعامل معها بنفس المضاد. ومن أبرز الأسباب التي تدفع الأفراد إلى اللجوء إلى التداوي الذاتي: آلام الحلق. وفيما يتعلق بدور الصيدلي، أفاد %23فقط من الزبائن بعدم تمكنهم من اقتناء المضاد الحيوي من الصيدلية، بينما حصلت نسبة ضئيلة منهم على بديل مناسب للعلاج. وتُبرز هذه النتائج الحاجة ال ُم ِل ّحة إلى تكثيف حملات التوعية حول الاستخدام الصحيح للمضادات .الحيوية، بهدف الحد من انتشار هذه الظاهرة المقلقة